Juridical Analysis of Claims Procedures and Legal Consequences for Fraud Actions by the Hospital to BPJS Kesehatan in Inpatient Care with the INA-CBGS System - Krisna Krisna; Megawati Barthos; Zudan Arif Fakrulloh (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2021)
The government began to fulfill the right to health by establishing a health BPJS since January 1, 2014. The BPJS Kesehatan payment system for hospitals uses the INA-CBGs tariff payment system, which is payment with package rates covering all hospital components. Since the introduction of the National Health Insurance (JKN) in Indonesia, the potential for fraud in health services has expanded. This study aims to reveal the procedure for claims and legal consequences of fraud by the hospital against BPJS Kesehatan in hospitalization with the INA-CBGS system. This research is a normative legal research and empirical law, namely research conducted by collecting legal materials both primary, secondary and or tertiary.